2016
DOI: 10.1016/j.jval.2016.09.1649
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Stroke: A Systematic Review on Post-Stroke Care

Abstract: PHC reported its HRQoL. Pain/Discomfort (50.7%) and Anxiety/Depression (38.8%) were dimensions in which users reported more often some problem. About 10% of users reported extreme problems in these dimensions. A worse HRQoL was significantly associated with the following factors: women (β = -0,012); stroke (β = -0,106), arthritis, osteoarthritis or rheumatism (β = -0,086), depression (β = -0,079), heart diseases (β = -0,032); diet to lose weight (β = -0,014); diet to reduce fat intake (β = -0,017); health self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 0 publications
0
32
0
6
Order By: Relevance
“…Stroke was the second most frequent cause of death and the third most frequent cause of disability worldwide. In a recent systematic review, poststroke care costs per patient month were estimated to range from $752 in Australia to $4850 in the USA, underlining the substantial overall economic burden associated with this neurological condition [2]. Altogether, these findings clearly demonstrate the importance of better stroke prevention in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke was the second most frequent cause of death and the third most frequent cause of disability worldwide. In a recent systematic review, poststroke care costs per patient month were estimated to range from $752 in Australia to $4850 in the USA, underlining the substantial overall economic burden associated with this neurological condition [2]. Altogether, these findings clearly demonstrate the importance of better stroke prevention in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, stroke is a leading cause of mortality and disability, and the substantial economic costs for poststroke care and treatment are needed [ 1 ]. A study from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) showed that stroke is the second largest cause of death worldwide (5.5 million (95% UI 5.3–5.7)) in 2016, and the overall burden of stroke remains high [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke itself can result in minor to major, short and longterm physical disabilities [1], cognitive impairments [2,3], emotional disturbances [4,5], decreased social interactions [6] and excessive economic burden [7]. In addition to neurological problems appearing in the immediate post-stroke period [8], often there are multiple late complications [9] which should not to be neglected.…”
Section: Introductionmentioning
confidence: 99%